ANALYTICAL PERFORMANCE SPEKTROFOTOMETER UV-VIS DOUBLE BEAM DENGAN METODE KIT SPADNS (SODIUM 2-(PARASULFOPHENYLAZO)-1,8-DIHYDROXYNAPHTHALENE-3,6-DISULFONATE) PADA PENGUJIAN KADAR FLUORIDA (F-) AIR MINUM DALAM KEMASAN DI KALIMANTAN TIMUR - Anissa Tsunami; Bohari Yusuf; Moh. Saiful Arif (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Fluoride is an important element in the human body that functions to maintain healthy teeth and bones. However, excessive fluoride levels can cause fluorosis, while low levels increase the risk of dental caries. This study aims to determine the fluoride ion content in various types of drinking water using the UV-Vis spectrophotometry method with the SPADNS reagent kit and to determine the limit of detection (LoD) and limit of quantification (LoQ) values. The research procedure included preparing standard solutions, calibration curves, optimizing reaction time and pH, and applying the method to bottled drinking water (AMDK), refill water, and PDAM water samples. The results showed a maximum wavelength of 570 nm, an optimum reaction time of 1 minute, and an optimum pH of 5.0–5.5. The LoD and LoQ values were 0.00923 mg/L and 0.0327 mg/L, respectively, indicating high sensitivity of the method. The fluoride content in AMDK 01 (Sijiro) was 0.11 mg/L, AMDK 02 (DC) was 0.12 mg/L, refill water was 0.59 mg/L, and PDAM water was 1.19 mg/L. All results were below the maximum limit of 1.5 mg/L (SNI 3553:2015; WHO), making them safe for consumption. The double-beam UV-Vis spectrophotometry method with SPADNS reagent proved to be sensitive, precise, and accurate for determining fluoride levels in drinking water. Keywords: Fluoride, KIT SPADNS, UV-Vis Spectrophotometry, Drinking Water